Revision Surgery and Progression to Total Hip Arthroplasty After Surgical Correction of Femoroacetabular Impingement: A Systematic Review - Migliorini, Filippo; Maffulli, Nicola; Baroncini, Alice; Eschweiler, Jorg; Tingart, Markus; Betsch, Marcel (American Journal of Sports Medicine, 2022)
Background: Femoroacetabular impingement (FAI) is a major cause of hip pain in young adults and athletes. Surgical treatment of FAI is recommended in cases of failed nonoperative treatment that have the typical clinical and radiographic findings. At present, the role of risk factors for revision surgery and progression to total hip arthroplasty (THA) in patients with FAI is still unclear. Purpose: To investigate the possible association between (1) rate of revision and progression to THA and (2) patient characteristics, type of lesion, family history of hip disease, type of intervention, radiographic parameters, physical examination, and pre- and postoperative scores. Study Design: Systematic review; Level of evidence, 4. Methods: The present systematic review was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. In October 2020, the main online databases were accessed. All articles concerning surgical correction for selected patients with FAI were accessed. Patient characteristics, type of intervention, radiographic parameters, physical examination, and pre- and postoperative scores were assessed. The outcomes of interest were the possible association between these variables and the rate of revision and subsequent progression to THA using a multivariate analysis through the Pearson product-moment correlation coefficient. Results: Data from 99 studies (9357 procedures) were collected. The median follow-up was 30.9 months (interquartile range, 24.0-45.0). The mean ± SD age was 33.4 ± 9.3 years; mean body mass index (BMI), 24.8 ± 4.8; percentage right side, 55.8% ± 8.0%; and percentage female sex, 47.5% ± 20.4%. The overall rate of revision was 5.29% (351 of 6641 patients), while the rate of subsequent progression to THA was 3.78% (263 of 6966 patients). Labral debridement (P <.0001), preoperative acetabular index (P =.01), and BMI (P =.03) all showed evidence of a statistically positive association with increased rates of THA. No other statistically significant associations were found between patient characteristics, type of lesion, family history of hip disease, type of intervention, radiographic parameters, physical examination, or pre- and postoperative scores and the rate of revision and/or progression to THA. Conclusion: Although surgical procedures to treat FAI led to satisfactory outcomes, there was a revision rate of 5.29% in the 9357 procedures in the present systematic review. The rate of progression to THA after a median follow-up of 30 months was 3.78%. Patients who have a higher BMI and/or have a pathologic acetabular index and/or undergo labral debridement during correction of FAI are more at risk for a subsequent THA. We advocate additional education of this patient population in terms of expected outcomes and suggest surgical labral repair instead of debridement if needed.
CRIS-Team Scopus Importer:2022-07-20
Keywords: femoroacetabular impingement; revision surgery; risk factors; total hip arthroplasty